Cut-edge corrosion behavior assessment of newly developed environmental-friendly coating systems using the Scanning Vibrating Electrode Technique (SVET) - Geraint Williams (Corrosion Science, 2021)
Accelerated cut-edge corrosion performance of commercialized full waterborne coating systems containing enviro-friendly corrosion inhibitors was studied on 55 wt% Al, 44 wt% Zn and 1 wt% Si galvanized steel in 5 wt% NaCl solution at ambient temperature via the Scanning Vibrating Electrode Technique (SVET). At the same volume content (7–11 wt%), benzotriazole pigments had a better overall cut-edge corrosion performance than calcium ion exchanged silica pigments. It was due to benzotriazole’s superior cathodic protection of the cut-edge in comparison with calcium silicate. Furthermore, although both enviro-friendly inhibitors did not exhibit the same performance level as the conventional Cr(VI)-containing system, they exhibited promising results in inhibiting cut-edge corrosion in a fully commercialized waterborne coating system.